Image analysis : 21st Scandinavian Conference, SCIA 2019, Norrköping, Sweden, June 11-13, 2019 : proceedings /: 21st Scandinavian Conference, SCIA 2019, Norrköping, Sweden, June 11-13, 2019 : proceedings. ([2019]) - Unknown
No abstract available